ANALISIS FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR PERIODE 2017-2019 - Yunilia, Inda; Sha, Thio Lie (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of investment decision, managerial ownership, company growth, and profitability on the value of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sample selected by purposive sampling method and valid data is 25 companies. The data processing technique uses multiple regression analysis assisted by the Eviews 12 and Microsoft Excel program. The results of this study indicate that investment decision has a significant positiveeffect on firm value, while managerial ownership, company growth and profitabilityhave a insignificant positive effect on firm value. The implication of this research shows that the importance of company value for investors is necessary to increase the company's performance in order to attract investors to invest.